Autonomy, rights and children with special needs: a new paradigm, 2017-2019 - Riddell, Sheila (UK Data Service, 2021)
This research investigated the way in which the children's rights agenda is being implemented in practice in the field of SEN/ASN, taking into account the wider policy context of declining budgets, reduced local authority power, increasingly complex governance arrangements and policy divergence across England and Scotland. The project's specific objectives are to analyse: The extent to which children and young people with SEN/ASN in different social, geographical and educational contexts and with different types of difficulty are able to realise their rights effectively; The degree to which the rights of children and young people with SEN/ASN intersect with those of parents/carers and are driven by, or influence, the decision-making of schools and local authorities; The way in which capacity for autonomous decision-making is understood and acted upon in different social and educational contexts; The factors which promote or inhibit the realisation of rights by children and young people with SEN/ASN, including those who are looked after by the local authority; The impact of a children's rights approach on the broader education and social policy landscape. Since the late 1970s, in the field of special educational needs (SEN) in England and additional support needs (ASN) in Scotland, there has been a growing focus on parental involvement in educational decision-making. Despite the emphasis on the empowerment of children in the UN Convention on the Rights of the Child (UNCRC) and the UN Convention on the Rights of Persons with Disabilities (UNCRPD), parental rights in education have tended to trump those of children and young people. There has also been some disparity with regard to the emphasis on the educational rights of children and young people with SEN/ASN in different parts of the UK, and competing understandings of the concept of autonomy. In both England and Scotland, new legislation aims to place the rights of children and young people with SEN and ASN on a par with those of their parents. In the light of this change, this research will consider whether we are witnessing a paradigm shift in the field of special and additional support needs analagous to that which occurred in state education in the 1980s and 1990s, when marketisation and consumerism attained a much higher profile. The research addresses important questions with regard to: the practical realisation of the rights of children and young people with different types of difficulty and in different social and geographical contexts; the way in which children and young people's rights sit alongside those of their parents; the measures which may be taken by schools and local authorities to promote the rights of children and young people. In considering the way in which the rights of children and young people with SEN/ASN are implemented in England and Scotland, the research took account of changes in the wider social policy landscape, including the ongoing impact of devolution, growing diversity of governance arrangements in English schools and public sector austerity. A range of research methods were used in this project, including analysis of policy, legislation and administrative data; a survey of local authority policy and practice in relation to the rights of children and young people; key informant interviews to elicit views on the factors which were likely to promote or inhibit the realisation of the rights of children and young people with SEN/ASN; qualitative work with children and young people and their parents/carers in home and school settings. Since the late 1970s, in the field of special educational needs (SEN) in England and additional support needs (ASN) in Scotland, there has been a growing focus on parental involvement in educational decision-making. Despite the emphasis on the empowerment of children in the UN Convention on the Rights of the Child (UNCRC) and the UN Convention on the Rights of Persons with Disabilities (UNCRPD), parental rights in education have tended to trump those of children and young people. There has also been some disparity with regard to the emphasis on the educational rights of children and young people with SEN/ASN in different parts of the UK, and competing understandings of the concept of autonomy. In both England and Scotland, new legislation aims to place the rights of children and young people with SEN and ASN on a par with those of their parents. In the light of this change, this research will consider whether we are witnessing a paradigm shift in the field of special and additional support needs analogous to that which occurred in state education in the 1980s and 1990s, when marketisation and consumerism attained a much higher profile. The research addresses important questions with regard to: (1) the practical realisation of the rights of children and young people with different types of difficulty and in different social and geographical contexts; (2) the way in which children and young people's rights sit alongside those of their parents; (3) the measures which may be taken by schools and local authorities to promote the rights of children and young people. In considering the way in which the rights of children and young people with SEN/ASN are implemented in England and Scotland, the research will take account of changes in the wider social policy landscape, including the ongoing impact of devolution, growing diversity of governance arrangements in English schools and public sector austerity. A range of research methods will be used in this project, including analysis of policy, legislation and administrative data; a survey of local authority policy and practice in relation to the rights of children and young people; key informant interviews to elicit views on the factors which are likely to promote or inhibit the realisation of the rights of children and young people with SEN/ASN; qualitative work with children and young people and their parents/carers in home and school settings.